Levels and congener distributions of PCDDs, PCDFs and Co-PCBs in Japanese retail fresh and frozen vegetables - Amakura, Y. (National Inst. of Hygienic Sciences, Tokyo (Japan)); Tsutsumi, T; Sasaki, K; Maitani, T (Food Hygiene and Safety Science (Shokuhin Eiseigaku Zasshi), 2003)
To evaluate dioxin contamination in retail vegetables, congener analyses of polychlorinated dibenzo-p-dioxins (PCDDs), polychlorinated dibenzofurans (PCDFs) and coplanar polychlorinated biphenyls (Co-PCBs) were performed on sixty varieties of fresh vegetables including cereals and mushrooms, obtained from Japanese supermarkets in 2002. The toxic equivalent quantity (TEQ) levels for dioxins in samples ranged from < 0.001 to 0.089 pg-TEQ/g wet weight, when undetected and trace were taken as zero. Among the samples, dioxins were generally detected in green leafy vegetables. The highest TEQ value was for mulukhiya (0.089 pg-TEQ/g), followed by spinach and komatsuna (Japanese mustard spinach) (0.077 and 0.074 pg-TEQ/g, respectively). Additionally, the dioxin levels in seventeen varieties of frozen vegetables were also determined, and showed TEQ values ranging from<0.001 to 0.080 pg-TEQ/g. The total TEQ in commercial vegetables mainly reflected the levels of 1,2,3,7,8-PeCDD, 2,3,4,7,8-PeCDF and 3,3',4,4',5-PeCB (#126) (the sum of them represented 63% of the total TEQ).